Address by the Duke of York at the opening of Parliament House, Canberra - George VI, King of Great Britain, 1895-1952. (1927)
Address by the Duke of York at the opening of Parliament House in Canberra, 9 May 1927. The address was given to the members of both Houses, who were assembled in the Senate chamber (Journals of the Senate, 9/5/1927, p.234). In his address, the Duke explains his special commission from King George V to attend the day's ceremony. The Duke sends greetings from the King, who fondly remembers his previous visit to Australia in 1901 and hopes that Australia will have prosperity and advancement in future years.
Manuscript reference no.: MS 1604.
The document, while held by the National Library of Australia, is owned by the Australian Senate. Further information may be obtained from the Director, Legislation and Documents, Table Office, Department of the Senate, Parliament House.
Also available online
The opening of the provisional Parliament House was a gala occasion. Invitations were issued to 500 national and international official guests and a further 5000 tickets were distributed throughout Australia for seats in outside stands. The ceremony included the review of a guard of honour by the Duke of York, later King George VI and Queen Elizabeth, the Queen Mother and a reading in the Senate chamber of an address from King George V. After the official proceedings, a review of 2000 troops and a Royal Australian Air Force flypast were held in York Park- National Archives of Australia.
Keywords: George -- V, -- King of Great Britain, -- 1865-1936.; George -- VI, -- King of Great Britain, -- 1895-1952.; Parliament House (Canberra, Australia); Royal visitors -- Australia; Australia -- Politics and government